2021
DOI: 10.1590/1516-3180.2021.0138.r2.120321
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lifestyle on health-related quality of life among young university students: a cross-sectional study

Abstract: BACKGROUND: Lifestyle is strongly involved in the pathogenesis and progression of noncommunicable diseases, and has a great impact on quality of life. The goal of the present study was to analyze the lifestyle and body composition (BC) of young university students during the pandemic, and their relationship with health-related quality of life (HrQoL). DESIGN AND SETTING: Observational cross-sectional study conducted in the Universidad Europea de Madrid, Spain. METHODS: A total sample of 56 healthy university s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…The RSEG participants improved the specific categories of HrQoL of vitality, general health, and physical component summary over time with a large effect size for these three variables, while the ISEG improved the general health with a large effect size. No significant differences were found between both interventions, so both groups showed a similar improvement in HrQoL, even though during the COVID-19 pandemic the university community presented very low levels of HrQoL [56].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The RSEG participants improved the specific categories of HrQoL of vitality, general health, and physical component summary over time with a large effect size for these three variables, while the ISEG improved the general health with a large effect size. No significant differences were found between both interventions, so both groups showed a similar improvement in HrQoL, even though during the COVID-19 pandemic the university community presented very low levels of HrQoL [56].…”
Section: Discussionmentioning
confidence: 81%
“…As well as the participants of the RSEG and the ISEG improved their PA levels and their eating habits, their HrQoL also increased. In this regard, some observational studies have found positive correlations between HrQoL and PA levels [31] and adherence to the Mediterranean diet [29], while others do not [56]. The RSEG participants improved the specific categories of HrQoL of vitality, general health, and physical component summary over time with a large effect size for these three variables, while the ISEG improved the general health with a large effect size.…”
Section: Discussionmentioning
confidence: 94%
“…14 In observational studies, HrQoL has shown positive correlations with the adherence to the Mediterranean diet 15 and with physical activity levels, 16 as well as negative correlations with sedentary behavior. 17 However, to date, very few studies analyze the correlations between multiple aspects of lifestyle, body composition, and HrQoL.…”
Section: Introductionmentioning
confidence: 99%
“…Having a healthy lifestyle contributes to improving the health-related quality of life (HrQoL), its impact being even higher than that of socioeconomic factors 14 . In observational studies, HrQoL has shown positive correlations with the adherence to the Mediterranean diet 15 and with physical activity levels, 16 as well as negative correlations with sedentary behavior 17 . However, to date, very few studies analyze the correlations between multiple aspects of lifestyle, body composition, and HrQoL.…”
Section: Introductionmentioning
confidence: 99%
“…To date, few studies have been conducted with patients with TTH that report a broad analysis of the associated psychosocial aspects, analyzing their impact on the severity of this pathology [20][21][22]. In addition, TTH is common among people who spend much sitting time at work, like university employees [23,24], and the World Health Organization global action plan on workers' health establishes that lifestyle interventions should be carried out within the workplace [25].…”
Section: Introductionmentioning
confidence: 99%